A Whole Education Approach to Education Reform in Barbados: Effective Provision for Students with Special Educational Needs and Disabilities - Garry Hornby (MDPI AG, 2023)
Improving education provision for children with special educational needs and disabilities in Barbados is the focus of this article. It takes into account the wider historical and educational context and uses a whole education approach to conduct the analysis and propose transformation of the education system, involving three key components. First, abandoning the system of selective secondary education based on the results of a high-stakes examination, the 11 plus, and replacing it with a more equitable system of geographical zoning. Second, revamping curricula at primary and secondary schools to emphasise the development of literacy, numeracy, interpersonal and vocational skills rather than focusing mainly on preparing students for academic examinations, especially the 11 plus examination. Third, implementing comprehensive policy and procedures for the identification and effective education of children with special educational needs and disabilities in order to maximise outcomes for all students.